Studies on the Efficacy of Twenty-Five-Hydroxycholecalciferol to Prevent Tibial Dyschondroplasia in Ross Broilers Fed Marginal Calcium to Market Age - Roberson, K.D.; Ledwaba, M.F. (International Journal of Poultry Science, 2005)
Two experiments were conducted to evaluate the effect of 25-hydroxycholecalciferol [25-(OH)D3] on tibial dyschondroplasia (TD) in broilers grown to market age. In Experiment 1, Ross cockerels were fed a mash diet marginal in calcium and adequate in phosphorus and cholecalciferol to 35 days of age in battery cages. Dietary 25-(OH)D3 was fed at 0 or 40 ug/kg during the starter (1-17 days) and grower (18-35 days) phases. During the grower phase, there was third treatment in which 25-(OH)D3 was fed to 17 days of age and then the control diet was fed to 35 days of age. Phytate phosphorus retention was measured at the end of each phase. In Experiment 2, Ross straight-run broilers were grown on litter and fed marginal calcium diets that were either crumbled (starter, 1-16 days) or pelleted (grower, 17-42 days; finisher 43-49 days). Dietary 25-(OH)D3 was fed at 0 or 69 ug/kg or a third treatment consisted of 69 ug/kg 25-(OH)D3 to 16 days and the control diet to 49 days of age. Dietary 25-(OH)D3 did not affect growth performance or incidence of TD in either experiment. In Experiment 1, phytate phosphorus retention was increased by feeding 25-(OH)D3 only in the grower phase. Bone ash at 35 days in Experiment 1 and bone strength at 48 days in Experiment 2 were not affected. The results show that Ross broilers have a low incidence of TD when marginal calcium is fed and do not require dietary 25-(OH)D3 to prevent TD or improve bone strength.